Process of the selective reduction and recovery of iron from copper tailings - SHAO Shuang; XING Peng; ZHANG Wen-juan; MA Bao-zhong; WANG Cheng-yan; CHEN Yong-qiang; WANG Ling (工程科学学报)
Copper tailings are potential resources rich in iron minerals and their long-term stockpiling not only cause resource waste but also bring serious pressure to the ecological environment. Therefore, the resource utilization of copper tailings has attracted considerable attention and becomes the key to the sustainable development of the copper industry. In this study, the technology of the selective reduction of iron from copper tailings at low temperature using coal and recovery of iron from reduction pellets using magnetic separation was proposed. The effects of several factors, such as reduction temperature, reducing agent dosage, reduction time, and activator dosage, on the selective reduction and recovery of iron from copper tailings were investigated. The following optimum process conditions are determined through single-factor experiments: the reduction temperature is 1200℃, the reducing agent dosage is 25% of the mass of copper tailings, the reduction time is 2 h, and the activator dosage is 5% of the mass of copper tailings. Under the optimum process conditions, the iron mass fraction of the magnetic concentrate exceeds 90%, and the iron recovery rate is greater than 95%. The composition and structure of copper tailings, reduction pellets, and magnetic ores were determined via X-ray diffraction, optical microscopy, and scanning electron microscopy. Moreover, the mechanism of mineral phase reduction and metal phase generation/merging was revealed. The results show that increase in temperature is beneficial for the reduction, merging, and growth of the metal phase. Merging the metal particles becomes common by increasing the reducing agent dosage. Prolonging the reduction time promotes the merging of metal particles and reduction of fayalite. The activator promotes the diffusion and merging of metal particles. The merging and growth of metal particles promote the increase in particle size. The amount of slag wrapped by coarse metal particles in the magnetic concentrate is relatively small in the magnetic separation process, and the iron grade of the magnetic concentrate is significantly improved.